AN INTRODUCTION TO THE MUSIC OF HELEN GRIME. (July 2019) - Carey, Christian
Abstract: This article examines the music of composer Helen Grime. It discusses her use of melodic and harmonic materials derived from a Bothy Ballad in Two Eardley Pictures. It analyzes the frequent use of interpenetration and stratification in her music, and the morphing of motivic material via a number of transformations in her Violin Concerto. Finally, the article discusses the narrative quality found in Grime's Piano Concerto.